Hydrolysis of cellulose to fermentable sugars by using 2, 5-furandicarboxylic acid as a recyclable catalyst in green solvent of GVL/ H2O. (October 2022) - Sun, Linhao; Lu, Xuebin; Xue, Yudan; Wang, Xiaotong; Yu, Zhihao; Du, Xinyuan; Zhang, Rui; Li, Xiaoyun; Xiong, Jian
Abstract: Hydrolysis of cellulose into C6 sugars is the starting point and entry point for biomass refining and is an important pathway for biofuel production. However, biomass-based 2, 5-furandicarboxylic acid (FDCA) is a highly catalytic promising but underutilized organic carboxylic acid. In this paper, we investigated the use of easily recoverable FDCA as a catalyst for the hydrolysis of cellulose to produce C6 sugars in a γ-valerolactone/water (GVL/H2 O) green solvent system. FDCA has high inherent acidity (pKa = 2.76) and stability with unique solubility in aqueous solutions and many solvents. These properties allows it to meet both high temperature solubility for efficient homogeneous hydrolysis reactions and low temperature crystallization catalysts for high purity recovery. This process not only solves the problem of solid-solid mass transfer between solid acid and cellulose which limits the hydrolysis rate, but also eliminates the problem of difficult separation and recovery of liquid acid catalysts. The results showed when initial concentration of microcrystalline cellulose was 0.7 wt%（equivalent to 7 g/L）, and the initial dosage of FDCA was 2.0 wt%, the maximum yield of C6 sugars reached 72.9% (40.1% glucose and 32.8% fructose) in GVL/H2 O (60/40, V/V) with a reaction at 200 °C for 30 min. More importantly, FDCA can achieve 80% recovery and ＞99% spectroscopic purity recovery. This study reveals the potential of FDCA as a catalyst in the catalytic conversion of biomass, which provides a new pathway for the green and efficient conversion of biomass resources. Graphical abstract: Image 1 Highlights: Using FDCA with special solubility as catalyst for cellulose hydrolysis reaction. Application of green GVL/H2 O solvent system to cellulose hydrolysis reaction. High efficiency and high purity recovery of catalyst from the reaction system. Realizing the green conversion and sustainable utilization of biomass energy. Proposing the application prospect of PC/H2 O solvent system in biomass conversion.